Foot Exercise for Managing Neuropathic Pain in the Elderly - Pratiwi, Wahyu Nur; Gayatri, Paramita Ratna; Isnaeni, Ely; Pratama, Yuan Guruh; Firmanda, Giovanni Iga; Lin, Chu-eh Ho (STIKES Adi Husada, 2024)
Elderly people often experience neuropathic pain in the extremities of the feet which is caused by decreased blood vascularization in the feet. One effort that can be made to increase blood vascularization in the feet is by doing foot exercises. This study aims to determine the effect of foot exercises on pain conditions due to neuropathy experienced by the elderly. This research was Quasi-experimental research with 22 elderly people who met certain criteria and then divided into control and intervention groups. Variable which is pre and post-test neuropathic pain data were obtained using the Numeric Rating Scale instrument in the observation sheet. The Wilcoxon signed-rank test in the intervention group showed a p-value = 0.003, while in the control group the p-value= 0.643. These results indicate that the change in neuropathic pain was significant in the intervention group after being given foot exercises. Foot exercise movements have a relaxing effect on the feet, thereby stimulating the production of endorphin hormones. Endorphin hormones play a role in blocking substance P which plays a role in triggering pain. This blocked substance P results in the transmission of pain impulses in the spinal cord being hampered so that the intensity of neuropathic pain in the lower extremities can decrease.